Effect the Influence of Tobacco Advertisements on Social Media and Religiosity Smoking Perception Among High School Students in Medan - Sarah Mumtaz; Putra Apriadi Siregar; Zuhrina Aidha (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Tobacco advertisements on social media are one of the marketing tools used by the tobacco industry to attract teenagers to smoke. The purpose of this study was to see how the influence of tobacco advertisements on social media and religiosity on the perception of smoking in adolescents, especially in the Islamic Senior High School Model 2 Medan. This study used quantitative research with a cross-sectional design. This research was conducted at Islamic Senior High School Model 2 Medan from January to February 2024. The population in this study was 2,203, and the sampling technique used was a purposive sampling of 1.000 respondents. The variables studied in this study include tobacco advertising, smoking perceptions, and religiosity with the research instrument, namely a questionnaire. The data will be tested for validity and reliability and then will be processed with correlation tests and multiple linear regression tests using the SPSS Version 20 application. The results of this study indicate that there is an influence of tobacco advertisements on social media on adolescents' perceptions of smoking behavior (Sig < 0.005, t = 3.553) and there is an influence of religiosity on adolescents' perceptions of smoking behavior (Sig < 0.005. t = 2.809). Tobacco advertising is the most dominant influence on the perception of smoking. While religiosity also affects the perception of smoking. Therefore, efforts can be made to implement policies that prohibit tobacco promotion in the school environment, including on official school social media, and to develop educational programs that strengthen religiosity values and increase social media literacy among students Keywords: Adolescents, Perception, Religiosity, Social Media, Tobacco advertisements